Extracellular matrix glycoproteins of skin fibroblasts in tuberous sclerosis - Uysal, Hamdi (1995)
The first main objective of this project was to isolate cellular fibronectin from cultures of skin fibroblasts derived from tuberous sclerosis (TS) patients and normals and to compare their structures, paying particular attention to the content and pattern of carbohydrate (glycosylation). The second main objective of this project was to establish the expression and localisation of glycoproteins fibronectin, laminin and tenascin of the extracellular matrix (ECM) in cultures of skin fibroblasts derived from patients with TS and normal individuals. In order to achieve these objectives, fibroblasts were established from primary cultures of skin explants of patients with TS. Control cells were cultured from skin explants donated by people not known to be suffering from any disorder. The purification of cellular fibronectin was achieved from conditioned medium of skin fibroblasts of TS patients and control fibroblasts using Prosep-gelatin affinity chromatography and gel filtration chromatography techniques. Analysis of purified cellular fibronectin by high pH anion-exchange chromatography with pulsed amperometric detection (HPAEC-PAD) revealed that the carbohydrate portion of the fibronectin molecule was made up of galactose, mannose, glucosamine, galactosamine, sialic acid and fucose. An increased concentration of sialic acid, galactosamine, glucosamine, galactose and mannose was observed in purified fibronectin derived from neck and ungual fibromas of patients with TS. To provide a total increase of carbohydrates more than two fold in comparison to normal fibroblastsderived fibronectin. Purified cellular fibronectin from conditioned medium of fibroblasts grown from skin lesions of different TS patients and from normal skin fibroblasts did not express HNK-1 (anti-leu 7) carbohydrate epitope. Normal skin fibroblasts showed an altered morphology and less confluence when grown on cell culture plates coated with cellular fibronectin derived from TS fibroblasts compared with control fibronectin. This may be a consequence of an altered glycosylation of this protein. The amino acid composition of the purified fibronectin from TS fibroblasts was very similar to that purified fibronectins from normal fibroblasts and to standard commercial plasma and cellular fibronectins. Laminin and tenascin were partially purified from conditioned cell culture medium demonstrating their synthesis and secretion into the cell culture medium by dermal skin fibroblasts. Expression and distribution of fibronectin, tenascin and laminin by established TS and normal skin fibroblasts using immunofluorescence, ELISA, and flow cytometry techniques were analysed and presented qualitative and quantitatively in this thesis. Increased expression and altered distribution of fibronectin and tenascin were observed in the fibroblasts derived from ungual fibroma lesion of a TS patient, but not in fibroblasts of neck fibroma, forehead plaque lesion or unaffacted skin of TS patients in comparison to control fibroblasts. However, increased expression and altered distribution of laminin were observed in neck fibroma-derived fibroblasts in contrast to fibronectin and tenascin. Laminin expression was not changed in ungual fibroma and forehead plaque lesion-derived fibroblasts in comparison to control fibroblasts. Altered distribution of fibronectin was well observed by immunofluorescence particularly in large cells of ungual fibroma. Similar differences were observed with laminin of cells from neck fibroma of TS patients. These results suggest the abnormal assembly of ECM in different TS skin lesions. Abnormal migration of cells during early embryonic development and the hardening of tissues associated with TS may result from abnormal assembly of the ECM. Alterations in distribution and structure of these adhesive glycoproteins may cause functional disruption in their binding and interactions with cells and ECM macromolecules. Studies of these changes in the ECM components may contribute to the understanding of the mechanisms involved in the aetiology of hardened tissues of TS.